Universal coverage of health services: tailoring its implementation - Guy Carrin; Inke Mathauer; Ke Xu; David B Evans (The World Health Organization, 2008)
In 2005, the Member States of WHO adopted a resolution encouraging countries to develop health financing systems capable of achieving and/or maintaining universal coverage of health services - where all people have access to needed health services without the risk of severe financial consequences. In doing this, a major challenge for many countries will be to move away from out-of-pocket payments, which are often used as an important source of fund collection. Prepayment methods will need to be developed or expanded but, in addition to questions of revenue collection, specific attention will also have to be paid to pooling funds to spread risks and to enable their efficient and equitable use. Developing prepayment mechanisms may take time, depending on countries' economic, social and political contexts. Specific rules for health financing policy will need to be developed and implementing organizations will need to be tailored to the level that countries can support and sustain. In this paper we propose a comprehensive framework focusing on health financing rules and organizations that can be used to support countries in developing their health financing systems in the search for universal coverage.